Factors associated with COVID-19 vaccine receipt at two integrated healthcare systems in New York City: a cross-sectional study of healthcare workers. Issue 1 (6th January 2022) - Oliver, Kristin; Raut, Anant; Pierre, Stanley; Silvera, Leopolda; Boulos, Alexander; Gale, Alyssa; Baum, Aaron; Chory, Ashley; Davis, Nichola J; D'Souza, David; Freeman, Amy; Goytia, Crispin; et al.
Abstract : Objectives: To examine the factors associated with COVID-19 vaccine receipt among healthcare workers and the role of vaccine confidence in decisions to vaccinate, and to better understand concerns related to COVID-19 vaccination. Design: Cross-sectional anonymous survey among front-line, support service and administrative healthcare workers. Setting: Two large integrated healthcare systems (one private and one public) in New York City during the initial roll-out of the COVID-19 vaccine. Participants: 1933 healthcare workers, including nurses, physicians, allied health professionals, environmental services staff, researchers and administrative staff. Primary outcome measures: The primary outcome was COVID-19 vaccine receipt during the initial roll-out of the vaccine among healthcare workers. Results: Among 1933 healthcare workers who had been offered the vaccine, 81% had received the vaccine at the time of the survey. Receipt was lower among black (58%; OR: 0.14, 95% CI 0.1 to 0.2) compared with white (91%) healthcare workers, and higher among non-Hispanic (84%) compared with Hispanic (69%; OR: 2.37, 95% CI 1.8 to 3.1) healthcare workers. Among healthcare workers with concerns about COVID-19 vaccine safety, 65% received the vaccine. Among healthcare workers who agreed with the statement that the vaccine is important to protect family members, 86% were vaccinated. Of those who disagreed, 25% received the vaccine (p<0.001). In a multivariable analysis, concern about being experimented on (OR: 0.44, 95% CI 0.31 to 0.6), concern about COVID-19 vaccine safety (OR: 0.39, 95% CI 0.28 to 0.55), lack of influenza vaccine receipt (OR: 0.28, 95% CI 0.18 to 0.44), disagreeing that COVID-19 vaccination is important to protect others (OR: 0.37, 95% CI 0.27 to 0.52) and black race (OR: 0.38, 95% CI 0.24 to 0.59) were independently associated with COVID-19 vaccine non-receipt. Over 70% of all healthcare workers responded that they had been approached for vaccine advice multiple times by family, community members and patients. Conclusions: Our data demonstrated high overall receipt among healthcare workers. Even among healthcare workers with concerns about COVID-19 vaccine safety, side effects or being experimented on, over 50% received the vaccine. Attitudes around the importance of COVID-19 vaccination to protect others played a large role in healthcare workers' decisions to vaccinate. We observed striking inequities in COVID-19 vaccine receipt, particularly affecting black and Hispanic workers. Further research is urgently needed to address issues related to vaccine equity and uptake in the context of systemic racism and barriers to care. This is particularly important given the influence healthcare workers have in vaccine decision-making conversations in their communities.